Living Qur'an Study on the Local Wisdom of the Pesantren Community Regarding the Rokat Sabe Tradition - Husna, Rifqatul; Ayu, Fitri (Santri: Journal of Pesantren and Fiqh Sosial, 2023)
The Qur’an, as a guide for every Muslim, is understood as a sentiment that is able to manifest the cultural behavior of society. In one study, understanding and meaning between the Al-Qur’an and life is called “living Qur’an”. This living Qur’an research discusses the use of Surah Al-Qadr as a talisman in farming in the rokat sabe tradition of the Dawuhan community, Probolinggo, which aims to describe how society emulates the function of the Al-Qur’an in everyday life. This type of research is qualitative research using descriptive-analytical inductive patterns. The research results show that this tradition is a tradition left by previous ancestors. In this tradition, people believe that Surah Al-Qadr is a reading that can bring glory and prosperity and can fertilize plants, based on Surah Al-Qadr, which means “glory”. This is consistent with Quraish Sihab’s argument in Tafsir Al-Misbah, which explains that the Al-Qur’an is noble; it was revealed to a nobleman (the prophet Muhammad), and its glory increased by being revealed on a noble night, too. Apart from that, local people are also famous for the term “santri nderek Kiai” because they have a santri spirit and are very obedient to kiai, who are considered religious figures and local regional leaders. This is proven by the existence of several religious rituals in the Rokat Sabe tradition, namely making the Surah Al-Qadr as a talisman for farming.